Physical status of human papillomavirus in the prognosis of recurrence of low-grade and-high-grade cervical intraepithelial lesions - M. K. Ibragimova; O. N. Churuksaeva; V. A. Bychkov; M. M. Tsyganov; I. V. Deryusheva; O. V. Shpileva; L. A. Kolomiets; N. V. Litviakov (Сибирский онкологический журнал, 2019)
The study included 168 patients with precancerous cervical lesions 37 with low-grade squamous intraepithelial lesions (LSIL), 131 with high-grade squamous intraepithelial lesions (HSIL), and 150 women, who had not abnormal cervical cell changes. All patients underwent full colposcopy assessment, cytological/histological examination, molecular detection and genotyping of high-risk human papillomavirus. Viral load and physical status of HPV-16 DNA was evaluated in cases of mono-infection (n=208). The prevalence of virus-positive cases among the patients with LSIL/NSIL and healthy women was 78.5 and 50.7 %, respectively. The frequency of recurrence in patients with LSIL and HSIL was found to be determined by the physical status of HPV-16. A significant difference in episomal, mixed and integrated forms of HPV-16 between patients with LSIL/HSIL and patients without abnormal cervical cell changes was found (p=0.0002).